2019
DOI: 10.12911/22998993/112482
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Z-ion Zeolite Substrate on Growth of Zea mays L. as Energy Crop Growing on Marginal Soil

Abstract: The presented study aimed at determining the influence of the increasing dose of new Z-ion zeolite substrate on the growth of maize (Zea mays L.) as species belonging to energy crops. In order to achieve the study aim, the pot experiment was carried out where the plants were grown on six series of media i.e.: on marginal soil (the control series I), on arable soil (the control series II) and on four mixtures of marginal soil with increasing Z-ion substrate addition (1%, 2%, 5%, 10 % v/v). The pot test was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Z‐ion substrate based on clinoptilolite zeolite was used as a nutrient carrier for maize crops. Results showed that the substrate seems to be an efficient means for fertilizer application of degraded or marginal soils increasing the above‐ground biomass of maize (Chomczyńska & Zdeb, 2019).…”
Section: Zeolites In Agriculture Applicationsmentioning
confidence: 99%
“…Z‐ion substrate based on clinoptilolite zeolite was used as a nutrient carrier for maize crops. Results showed that the substrate seems to be an efficient means for fertilizer application of degraded or marginal soils increasing the above‐ground biomass of maize (Chomczyńska & Zdeb, 2019).…”
Section: Zeolites In Agriculture Applicationsmentioning
confidence: 99%